THE EFFECT OF GUIDED QUESTION TECHNIQUE ON STUDENTS’ WRITING ACHIEVEMENT AT THE TENTH GRADE OF SMA NEGERI 1 BOMBANA - Nurfianti, Fifi; Jaya, Amir; Mursalim, Mursalim (Universitas Halu Oleo, 2020)
The aim of this research is to investigate the effectiveness of guided question technique on students’ writing achievement. This research used pre-experimental design with one group pre – test and post – test design. This study involved all students in class X MIA1 of SMAN 1 Bombana. The total sample was 29 students taken by using simple random sampling. The data of this research were collected by giving pre-test and post-test to the students in the form of written test. The data were analyzed by using SPSS 16.0 version by using descriptive analysis and inferential statistics. Result of data analysis indicated that guided question technique had positive significant effect on students’ writing achievement and could develop students’ skill in writing recount paragraph. It was based on result of descriptive analysis in which students’ pre test average score (mean) was 52,81, while mean of the post test score was 76,69. Moreover, result of probability value was .000 which was less than level of significant (05). It means that guided question technique is effective to develop the students’ achievement in writing.